Catalyst-free aza-Michael addition of azoles to 3-hydroxypyridine-based quinone methides. (9th January 2023) - Osipov, Dmitry V.; Korzhenko, Kirill S.; Osyanin, Vitaly A.
Abstract: We have studied the reaction of various 1 H -azoles with 2-((dimethylamino)methyl)pyridin-3-ol and 2-bromo-6-(hydroxymethyl)pyridin-3-ol as precursors of ortho - and para -quinone methides of 3-hydroxypyridine series, correspondingly. This process proved to be convenient and efficient for the synthesis of hybrid heterocycles containing both pyridine and azole moiety - 2- and 6-[(azolyl)methyl]pyridin-3-ols. The protocol has been successfully extended to 2, 6-bis-(hydroxymethyl)pyridine-3-ol, which is simultaneously ortho - and para -quinone methide precursor, involving both functionalities. Finally, two new heterocyclic systems 9 Н -pyrazolo[5, 1- b ]pyrido[2, 3- e ][1, 3]oxazine and 12 H -benzo[4, 5]imidazo[2, 1- b ]pyrido[2, 3- e ][1, 3]oxazine were obtained as a result of cascade aza-Michael/intramolecular nucleophilic substitution reactions from 2-((dimethylamino)methyl)pyridin-3-ol and 2-(methylthio)benzimidazole or 3, 4, 5-tribromopyrazole, correspondingly. Graphical abstract: Image 1